The enfacement illusion boosts facial mimicry. (February 2020) - Minio-Paluello, Ilaria; Porciello, Giuseppina; Gandolfo, Marco; Boukarras, Sarah; Aglioti, Salvatore M.
Abstract: Facial mimicry, the automatic imitation of another person's emotion, is a mechanism underlying emotion recognition and emotional contagion, a phylogenetically conserved form of empathy that precedes later developing empathic skills. We tested the possibility to increase facial mimicry by blurring self-other distinction via the enfacement illusion. To do so we delivered synchronous, versus asynchronous, visuo-tactile interpersonal multisensory stimulation on the observer and expresser's faces and then recorded surface facial EMG while participants observed videos of happy and sad facial expressions displayed by the expresser. Our results show that synchronous visuo-tactile stimulation can indeed enhance facial mimicry and that this depends on participants' baseline tendency to mimic.. Our findings could set the basis for developing novel interventions for conditions characterized by reduced empathic and emotion recognition skills, including autism and schizophrenia.